Genetic variant of AKT1 and AKTIP associated with late‐onset depression in a Brazilian population. (10th September 2013) - Pereira, Patricia Araújo; Bicalho, Maria Aparecida Camargos; de, Edgar Nunes; Malloy‐Diniz, Leandro; Bozzi, Isadora Cristine Reis Sguizzato; Nicolato, Rodrigo; Valadão, Daniela Rosa; Miranda, Debora Marques; Romano‐Silva, Marco Aurélio
<x xml:space="preserve">Abstract</x> Objectives Examine the association between polymorphisms in the AKT1 and AKTIP genes and late‐onset depression (LOD). Major depressive disorder is one of the most prevalent neuropsychiatric diseases. LOD is a disorder that starts after 65 years old. AKT1 is a downstream enzyme that has been implicated in the pathogenesis of neurotransmitter‐related disorders, such as depression. The identification of a novel AKT1‐binding protein (AKTIP) was pointed as an important new target. AKTIP binds directly to AKT1, enhancing the phosphorylation of regulatory sites, and this modulation are affected by AKT1 activation. The association of AKT1 and AKTIP polymorphisms with depressive symptoms was not investigated in LOD. Design Genotype tagSNPs in the AKT1 and AKTIP in LOD patients and controls. Settings An academic medical center. Participants Sample composed by 190 outpatients with LOD and 77 healthy individuals. Measures The participants were evaluated using Diagnostic and Statistical Manual IV criteria, MINI‐PLUS and the Geriatric Depression Scale. Results Our findings suggested an association between the tagSNP rs3730358 homozygous A/A (p = 0.006) and LOD. A strong association of allele A and increased association for LOD was demonstrated with tagSNP rs3730358 (p‐value = 0.003). Limitations Limitation include composition of our control group, where the exclusion criteria generated a kind of super‐healthy older group what might have produced a hidden stratification when compared with the LOD. Conclusion This study is the first one to establish the association of the AKT1/AKTIP genes and LOD, and further studies are necessary to clarify the functional role of these proteins. Copyright © 2013 John Wiley & Sons, Ltd.